Evaluasi Strategi Nasional Keamanan Siber Indonesia dalam Menanggapi Ancaman Digital Indonesia (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study aims to evaluate the effectiveness of Indonesia’s National Cyber Security Strategy in responding to increasingly complex and dynamic digital threats. In the midst of the digital transformation era, Indonesia’s cyberspace is vulnerable to various serious threats, such as ransomware attacks, data leaks, and the spread of disinformation that can disrupt social and political stability. This research adopts a qualitative- descriptive approach with content analysis of national strategic documents, reports from the National Cyber and Crypto Agency (BSSN), and compares them with cybersecurity policies in ASEAN countries. The results revealed that although BSSN has designed a relatively robust policy and institutional framework, its implementation is still faced with various serious obstacles, including fragmented regulations, lack of coordination between agencies, and limitations in terms of human resources. This study uses Dunn’s (2023) policy evaluation framework, covering the dimensions of effectiveness, efficiency, responsiveness, equity and sustainability. The study recommends the need to strengthen governance involving various sectors, increase awareness and cyber literacy among the public, and develop national capacity through public private partnership. This evaluation is expected to serve as a basis for policy formulation to strengthen Indonesia’s digital resilience, especially in the face of the increasing complexity of cyber threats at the national level.